2007
DOI: 10.1017/s0950268807008515
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing fasciitis in captive juvenileCrocodylus porosuscaused byStreptococcus agalactiae: an outbreak and review of the animal and human literature

Abstract: We observed an outbreak of necrotizing fasciitis associated with Streptococcus agalactiae infection in a group of juvenile saltwater crocodiles (Crocodylus porosus). We undertook screening of crocodiles and the environment to clarify the source of the outbreak and evaluated the isolates cultured from post-mortem specimens with molecular methods to assess clonality and the presence of known group B streptococcal virulence determinants. The isolates were indistinguishable by pulsed-field gel electrophoresis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 58 publications
(93 reference statements)
3
49
0
1
Order By: Relevance
“…To date, only serotypes Ia, Ib and III have been previously reported in fish (Vandamme et al, 1997;Evans et al, 2008;Suanyuk et al, 2008;Suwannasang et al, 2014). GBS is an emerging zoonotic agent isolated from piscine, dolphin, bovine, crocodile, camel and human sources (Ip et al, 2006;Bishop et al, 2007;Evans et al, 2008;Fischer et al, 2013). Multilocus sequence typing (MLST) of some GBS isolates from fish in Asia, including Thailand, indicated that these belong to sequence type (ST)-7/serotype Ia and ST-283/serosubtype III-4, which are associated with invasive disease of humans in Asia (Evans et al, 2008;Delannoy et al, 2013;Kayansamruaj et al, 2014).…”
Section: Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only serotypes Ia, Ib and III have been previously reported in fish (Vandamme et al, 1997;Evans et al, 2008;Suanyuk et al, 2008;Suwannasang et al, 2014). GBS is an emerging zoonotic agent isolated from piscine, dolphin, bovine, crocodile, camel and human sources (Ip et al, 2006;Bishop et al, 2007;Evans et al, 2008;Fischer et al, 2013). Multilocus sequence typing (MLST) of some GBS isolates from fish in Asia, including Thailand, indicated that these belong to sequence type (ST)-7/serotype Ia and ST-283/serosubtype III-4, which are associated with invasive disease of humans in Asia (Evans et al, 2008;Delannoy et al, 2013;Kayansamruaj et al, 2014).…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…GBS is an emerging zoonotic agent isolated from terrestrial and aquatic animals (Martinez et al, 2000;Duremdez et al, 2004;Bishop et al, 2007;Evans et al, 2008;Suanyuk et al, 2008;Fischer et al, 2013). In order to treat bacterial diseases in cultured tilapia, oxytetracycline is permitted for use in Thai aquaculture (Baoprasertkul et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the piscine isolates, the crocodile strain, QMA0336, isolated on a farm in the Northern Territory (Darwin) from a case of necrotizing fasciitis in a captive juvenile Crocodylus porosus (Bishop et al, 2007) is unrelated to the ST-261 group. It was identified as ST-23, serotype Ia, as were the two human isolates included in our study, collected from two cases of infection in Townsville, QMA0355 and QMA0357, which all belong to CC 23 ( Fig.…”
Section: Results and Discussion All Australian Piscine Isolates Belonmentioning
confidence: 91%
“…ST-23 is one of the major successful clones identified worldwide, the serotype Ia is associated in humans (Brochet et al, 2006), serotype III in dairy cattle (Brochet et al, 2006;Skov Sorensen et al, 2010), and it has been isolated from Scottish pinniped also serotype Ia, suggesting a possible transmission from human to grey seals via contaminated surface water (Delannoy et al, 2013). Establishing an unambiguous human origin of the Australian ST-23 serotype Ia in juvenile crocodiles remains to be confirmed (Bishop et al, 2007).…”
Section: Results and Discussion All Australian Piscine Isolates Belonmentioning
confidence: 99%
See 1 more Smart Citation